Mitos Tumbuhan Medis sebagai Simbol Bahan Narkotika dalam Film Dokumenter - Muhammad Aldy Febiansyah; Firmansyah; Dadi Ahmadi (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. The film How To Change Your Mind is a film whose title explains that we have to change our thinking when watching this film. This film tells about how Michael Pollan and also the narrator in the film tell and explain how psychedelics change our minds. Psychedelic which means